2017
DOI: 10.3345/kjp.2017.60.3.77
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and clinical characteristics of fever of unknown origin in children: a 15-year experience in a single center

Abstract: PurposeFever is one of the most common symptoms in children. In previous studies, infectious disease was the most common cause of pediatric fever of unknown origin (FUO). The aim of this study is to investigate the etiology, clinical characteristics and prognosis of pediatric FUO in 21 century with more diagnostics available and to analyze the factors for certain disease categories.MethodsAmong the children under 18 years old who were hospitalized at Samsung Medical Center from January 2000 to December 2014, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
10
0
3
Order By: Relevance
“…A study in a tertiary care Egyptian Hospital by Hassan RH showed infections to be the most common cause of FUO in 46 cases out of total 127 patients. 11 In studies done in Turkey, Italy and Taiwan 8,12,13,14,15 , similar trends were noted. Chien YL et al in Taiwan reported infections to be the dominant cause, followed by malignancy, miscellaneous causes and collagen vascular disease.…”
Section: Discussionsupporting
confidence: 64%
“…A study in a tertiary care Egyptian Hospital by Hassan RH showed infections to be the most common cause of FUO in 46 cases out of total 127 patients. 11 In studies done in Turkey, Italy and Taiwan 8,12,13,14,15 , similar trends were noted. Chien YL et al in Taiwan reported infections to be the dominant cause, followed by malignancy, miscellaneous causes and collagen vascular disease.…”
Section: Discussionsupporting
confidence: 64%
“…Undiagnosed causes are the most challenging cases worldwide. Kim et al [17] faced this challenge in 43% of their patients and accounted for 18.84% in our study. A recent study from our country reported that only 12.0% cases remained undiagnosed.…”
Section: Sixtymentioning
confidence: 81%
“…[13][14][15] En Corea del Sur se reportó que el porcentaje de niños en los que no se llegó a un diagnóstico fue de 43%, resultado similar al presente estudio. 16 Sin embargo, en otras series, el porcentaje de casos sin un diagnóstico final es menor. [13][14][15] Otro punto importante es que, en algunos casos, la etiología del FOD podría haberse identificado en establecimientos de menor nivel de complejidad, como las infecciones urinarias o fiebre tifoidea.…”
Section: Evolución De Pacientes Con Fodunclassified